2017
DOI: 10.3892/mmr.2017.8342
|View full text |Cite
|
Sign up to set email alerts
|

Effects of icariside II ameliorates diabetic cardiomyopathy in streptozotocin-induced diabetic rats by activating Akt/NOS/NF-κB signaling

Abstract: Icariside II is a flavonoid extracted from Epimedium that has antioxidant, anti‑inflammatory and antiapoptotic effects. The aim of the present study was to evaluate the effects icariside II on diabetic cardiomyopathy in streptozotocin-induced diabetic rats. Icariside II treatment improved body weight, heart/body weight ratio and fasting blood glucose in diabetic model rats. Icariside II was demonstrated to reduce the expression levels of creatine kinase and lactate dehydrogenase in serum, and to lower cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…A previous study showed that ICS II could attenuate myocardial fibrosis by inhibiting the NF-kB and transforming growth factor-β1/Smad2 signaling pathways ( 8 ). Another study indicated that ICS II ameliorated diabetic cardiomyopathy in streptozotocin-induced diabetic rats ( 9 ). However, the effects of ICS II on hypoxic-induced cardiomyocyte injury remained elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study showed that ICS II could attenuate myocardial fibrosis by inhibiting the NF-kB and transforming growth factor-β1/Smad2 signaling pathways ( 8 ). Another study indicated that ICS II ameliorated diabetic cardiomyopathy in streptozotocin-induced diabetic rats ( 9 ). However, the effects of ICS II on hypoxic-induced cardiomyocyte injury remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…ICS II has been reported to possess anti-inflammatory, antitumor and anti-osteoporotic properties ( 7 ). In recent years, ICS II has been found to exert various cardioprotective effects, such as the alleviation of myocardial fibrosis and diabetic cardiomyopathy ( 8 , 9 ). However, the specific roles and related molecular mechanisms of ICS II in hypoxia-induced H9c2 cells remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…For a comprehensive study in DMH it is essential to have a reliable and convenient animal model. STZ, the most widely used chemical to induce diabetes, selectively damages pancreatic cells, causes cell necrosis and results in reduced blood insulin and elevated blood sugar . However, systematic research on the development and examination of cardiac hypertrophy after diabetes onset is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is secreted by vascular endothelium, vascular smooth muscle cells, etc., and is associated with the degradation of IB by utilizing the in ammatory mediators which ultimately stimulate NF-κB, and when NF-κB is activated it can increase to some extent the binding to nuclear DNA, in turn acts on cardiomyocyte behavioral processes and leads to apoptosis [12][13][14]. In addition, NF-κB activates in ammatory cytokines including interleukins and tumor necrosis factor and further circulates to activate NF-κB itself, amplifying the local cascade response in this circulatory pattern and promoting the progression of myocardial injury [15][16][17]. The effects on the NF-B signaling pathway in diabetic cardiomyopathy rats were examined in this work.…”
Section: Discussionmentioning
confidence: 99%